Upaya Meningkatkan Pemahaman Bacaan Sholat pada Siswa Disleksia dengan Media Audio Visual dan Alat Peraga di SD Negeri Sumberadi - Tuminingsih, Tuminingsih; Fatimah, Siti; Subarkah, Imam; Awanis, Atsmarina (IAINU Kebumen, 2023)
This study aims to increase the understanding of dialexic children using audio-visual methodsand visual aids, this research uses Classroom Action Research (CAR) conducted at SD NegeriSumberadi grade 2 in Islamic Islamic Education learning prayer reading materials to increasestudent understanding in learning in research carried out during II cycle. The first cycleconsisted of 2 meetings and data collection techniques during the observation wereimplementation planning, observations and tests used during the research, the results showedthat in the first cycle, 55% of students who completed did not fulfill the KKM at the school andin the second cycle, completeness students reach 88% so it can be concluded that throughClassroom Action Research (CAR) to improve the reading comprehension of dyslexic childrenthere is an increase through audio-visual media and teaching aids.